Pengaruh Model Pembelajaran Kooperatif Tipe Make A Match Terhadap Hasil Belajar Matematika Sisiwa Kelas III di SDN 163 Palembang - Nina Eka Yuliana; Nurlaila Nurlaila; Siti Fatimah; Ahmad Syarifuddin; Suzana Paranita (Journal of Islamic Education, 2026)
This study aims to determine the effect of implementing the "make-a-match" cooperative learning model on the mathematics learning outcomes of third-grade students at SDN 163 Palembang. The population of this study was all third-grade students at SDN 163 Palembang. The sampling technique used random sampling, where 57 students were drawn from two classes to determine the control and experimental classes. The data collected in this study consisted of student learning outcomes obtained from pretest and posttest tests administered to third-grade students at SDN 163 Palembang. Data analysis used an independent sample t-test, meaning a two-sample unpaired test. The analysis showed a significant value of 0.000 <0.05, thus rejecting H0 and accepting Ha. Thus, the implementation of the Make-A-Match cooperative learning model has an impact on the mathematics learning outcomes of third-grade students at SDN 163 Palembang